Doctor Who : the official cookbook - Farrow, Joanna (Harper Design, an imprint of HarperCollinsPublisher, 2016)
Whether you're planning a party to watch the latest episode, need a showstopping cake that's bigger on the inside, or want to bite into the TARDIS at teatime, this is the ultimate collection of recipes from across space and time. Each of the forty recipes includes a colorful photograph and step-by-step instructions. Complete with baking templates in the back of the book, discover how to make cakes, sweets, and meals that are truly out of this world.